Forging Greater Xi'an: The Political Logic of Metropolitanization. (November 2016) - Jaros, Kyle A.
The trend of metropolitanization—rapid growth of the largest cities, horizontal sprawl, and pursuit of economic competitiveness—in China has attracted much attention from scholars. Whereas existing research generally portrays local governments as the key agents behind metropolitan-style development, this article emphasizes the active role higher-level governments play in shaping urban growth. I use the case of the Xi'an-Xianyang area in Shaanxi province to explore the political forces behind metropolitanization, tracing efforts since 2000 to build a larger, more integrated Greater Xi'an. I argue that provincial-level authorities in particular favor urban development that is focused on leading cities but crosses different jurisdictions, which helps them reap economic benefits from urban scale while limiting its political costs. Driving development from above is contentious, however, and requires significant clout on the part of provincial governments. In Xi'an, metropolitan growth has accelerated as Shaanxi has become economically and politically stronger, yet urban governance problems have persisted.